Planet Hunters TESS I: TOI 813, a subgiant hosting a transiting Saturn-sized planet on an 84-day orbit. Issue 1 (23rd January 2020) - Eisner, N L; Barragán, O; Aigrain, S; Lintott, C; Miller, G; Zicher, N; Boyajian, T S; Briceño, C; Bryant, E M; Christiansen, J L; Feinstein, A D; Flor-Torres, L M; et al.
ABSTRACT: We report on the discovery and validation of TOI 813 b ( TIC 55525572 b ), a transiting exoplanet identified by citizen scientists in data from NASA's Transiting Exoplanet Survey Satellite ( TESS ) and the first planet discovered by the Planet Hunters TESS project. The host star is a bright ( V  = 10.3 mag) subgiant ($R_\star =1.94\, R_\odot$, $M_\star =1.32\, M_\odot$ ). It was observed almost continuously by TESS during its first year of operations, during which time four individual transit events were detected. The candidate passed all the standard light curve-based vetting checks, and ground-based follow-up spectroscopy and speckle imaging enabled us to place an upper limit of $2\, M_{\rm Jup}$ (99 per cent confidence) on the mass of the companion, and to statistically validate its planetary nature. Detailed modelling of the transits yields a period of $83.8911 _{ - 0.0031 } ^ { + 0.0027 }$  d, a planet radius of 6.71 ± 0.38  R ⊕  and a semimajor axis of $0.423 _{ - 0.037 } ^ { + 0.031 }$  AU. The planet's orbital period combined with the evolved nature of the host star places this object in a relatively underexplored region of parameter space. We estimate that TOI 813 b induces a reflex motion in its host star with a semi-amplitude of ∼6 m s −1, making this a promising system to measure the mass of a relatively long-period transiting planet.